Gene transcription, neurotransmitter, and neurocognition signatures of brain structural-functional coupling variability - Lin Jiang; Sarah Genon; Jiayu Ye; Yan Zhu; Guangying Wang; Runyang He; Pedro A. Valdes-Sosa; Feng Wan; Dezhong Yao; Simon B. Eickhoff; Debo Dong; Fali Li; et al. (Nature Communications)
Abstract The relationship between brain structure and function, known as structural-functional coupling (SFC), is highly dynamic. However, the temporal variability of this relationship, referring to the fluctuating extent to which functional profiles interact with anatomy over time, remains poorly elucidated. Here, we propose a framework to quantify SFC temporal variability and determine its neurocognitive map, genetic architecture, and neurochemical basis in 1206 healthy human participants. Results reveal regional heterogeneity in SFC variability and a composite emotion dimension co-varying with variability patterns involving the dorsal attention, somatomotor, and visual networks. The transcriptomic signatures of SFC variability are enriched in synapse- and cell cycle-related biological processes and implicated in emotion-related disorders. Moreover, regional densities of serotonin, glutamate, γ-aminobutyric acid, and opioid systems are predictive of SFC variability across the cortex. Collectively, SFC variability mapping provides a biologically plausible framework for understanding how SFC fluctuates over time to support macroscale neurocognitive specialization.